BETWEEN CODEX AND PLATFORM; THE CHALLENGES OF DIGITIZATION IN HISTORY TEACHING: REFLECTIONS ON CMSP, TEACHER AUTONOMY, AND HISTORICAL CONSCIOUSNESS IN THE 21ST CENTURY (Editora Impacto Científico, 2025)
The Covid-19 pandemic accelerated the processes of digitization and structural reorganization of education, revealing historical inequalities in Brazil, especially in access to digital technologies. As an emergency response, the Government of São Paulo created the São Paulo Media Center (CMSP), initially intended to guarantee the continuity of education during social isolation. However, the platform surpassed its temporary character and consolidated itself as a central axis of São Paulo's educational policy, establishing a model based on platformization and the replacement of printed materials with multimodal digital content. This essay analyzes the impacts of this transformation on the teaching of History from two perspectives: the change of medium, from print to digital, and the reconfiguration of teacher autonomy. Drawing inspiration from authors such as Chartier, Manguel, Goulemot, Darnton, Santaella, and Rüsen, as well as recent studies on teaching work in Brazil; It is argued that reading on screens reorganizes interpretive gestures, making them more fragmented, while the logic of platforms intensifies control, bureaucratizes pedagogical practice, and reduces the teacher to an executor of pre-formatted content. In the case of History, this double transformation threatens the constitution of genetic historical consciousness (Rüsen), which depends on the critical mediation of the teacher and the reflective reading of sources. It is concluded that digitization and platformization, although irreversible, cannot be naturalized: their appropriation must be linked to the valorization of teachers, critical digital inclusion, and the preservation of pedagogical plurality, otherwise the historical and civic education of students will be impoverished.DOI: https://doi.org/10.56238/edimpacto2025.090-063